2017
DOI: 10.1186/s12864-017-3565-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles associated with cigarette smoking and moist snuff consumption

Abstract: BackgroundAmong the different tobacco products that are available on the US market, cigarette smoking is shown to be the most harmful and the effects of cigarette smoking have been well studied. US epidemiological studies indicate that non-combustible tobacco products are less harmful than smoking and yet very limited biological and mechanistic information is available on the effects of these alternative tobacco products. For the first time, we characterized gene expression profiling in PBMCs from moist snuff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…However, based on the location of differential methylation of a locus (Figure 4, cg17924476), AHRR expression may be up-regulated in buccal cells of SMK, and the tissue-specific level of gene expression requires further confirmation. Separately, we have shown that AHRR gene expression is upregulated in the peripheral blood mononuclear cells of SMK, relative to MSC and NTC from the same cohort (Arimilli et al 2017). Taken together, the AHRR pathway does not appear to be activated in MSC, suggesting that xenobiotic metabolism is differentially regulated between smokers and smokeless tobacco users.…”
Section: Discussionmentioning
confidence: 71%
“…However, based on the location of differential methylation of a locus (Figure 4, cg17924476), AHRR expression may be up-regulated in buccal cells of SMK, and the tissue-specific level of gene expression requires further confirmation. Separately, we have shown that AHRR gene expression is upregulated in the peripheral blood mononuclear cells of SMK, relative to MSC and NTC from the same cohort (Arimilli et al 2017). Taken together, the AHRR pathway does not appear to be activated in MSC, suggesting that xenobiotic metabolism is differentially regulated between smokers and smokeless tobacco users.…”
Section: Discussionmentioning
confidence: 71%
“…2 Smoking upregulates inflammatory mediators such as interleukin 6 and Creactive protein levels, possibly causing tissue damage. 3,4 Interestingly, gene expression levels remain elevated even up to 30 years after smoking cessation. 3,4 Not surprisingly, tendon tissue and the rotator cuff are also affected.…”
Section: See Related Article On Page 3181mentioning
confidence: 99%
“…3,4 Interestingly, gene expression levels remain elevated even up to 30 years after smoking cessation. 3,4 Not surprisingly, tendon tissue and the rotator cuff are also affected. Plachel et al 5 have demonstrated that changes in RNA expression profiles were correlated with chronic rotator cuff disorders but most strongly with age and severity of the rotator cuff pathology.…”
Section: See Related Article On Page 3181mentioning
confidence: 99%
“…We also filtered these search 78 results for datasets that reported the age, sex and smoking status of subjects. With this 79 additional search, we added 3 more datasets: GSE87072 [25], GSE47415 [26], and 22 of the 24 samples are duplicates from GSE47415 [26]. Our demographics files were 94 created to include variables that were reported across all samples (see merged 95 Demographics file DF1 of online supplementary data files) because study annotations 96 had not been uniformly reported in the databases (S1 File).…”
Section: Introductionmentioning
confidence: 99%